Hartmann & Kester's plant propagation : principles and practice.: principles and practice. (2013) - Hartmann, Hudson T (Hudson Thomas), 1914-1994; Kester, Dale E; Davies, Fred T, 1949-; Geneve, R. L
No abstract available